2018
DOI: 10.1016/j.chemosphere.2018.05.183
|View full text |Cite
|
Sign up to set email alerts
|

Response of phase I and II detoxification enzymes, glutathione, metallothionein and acetylcholine esterase to mercury and dimethoate in signal crayfish (Pacifastacus leniusculus)

Abstract: Metals and pesticides are common pollutants and the modulation of biomarkers can indicate sub-lethal influences on the physiology of organisms inhabiting impacted aquatic systems. We examined the effects of mercury and the organophosphate pesticide dimethoate on EROD, MROD, glutathione S-transferase (GST), acetylcholine esterase (AChE), metallothionein (MT) and glutathione (GSH) in the signal crayfish (Pacifastacus leniusculus). Crayfish were injected with mercury chloride or dimethoate (0.3, 0.6, 0.9 μg kg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The fail of fully reactivation by GSH pointed to inhibition mechanisms other than simple binding to SH-groups by toxic metals. In a recent study of Gunderson et al [83] in the signal crayfish Pacifastacus leniusculus a similar decrease of the GST activity in hepatopancreas cytosol was observed under Hg 2+ exposition at concentrations comparable to previous studies.…”
Section: Mercurysupporting
confidence: 79%
“…The fail of fully reactivation by GSH pointed to inhibition mechanisms other than simple binding to SH-groups by toxic metals. In a recent study of Gunderson et al [83] in the signal crayfish Pacifastacus leniusculus a similar decrease of the GST activity in hepatopancreas cytosol was observed under Hg 2+ exposition at concentrations comparable to previous studies.…”
Section: Mercurysupporting
confidence: 79%
“…MT participates in the storage, transport, and bioutilization of Zn, so a decreased expression of MT reduces the absorption efficiency of Zn in the body [ 36 ]. Moreover, MT2 is rich in reduced thiol groups (SH), which have a free radical scavenging capacity 100 times that of GSH, and can inhibit the release of mitochondrial cytochrome c and activate caspase-3 to reduce cell apoptosis and myocardial injury [ 37 , 38 ]. These were further confirmed by the present study where it was found that ZnLA administration increased the mRNA expression of ZNT-1, MT1A, and MT-2B and intracellular GSH-PX activity, but decreased LDH activity, cell apoptosis, and caspase-3 protein expression levels in IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Detoxifying enzymes such as esterase and glutathione S-transferases have a significant effect on pest resistance before pesticides. Consequently, impairing the function of such enzymes can reduce the likelihood of pest resistance to essential oils [114]. Furthermore, histological changes in the epithelial cells of insects' midguts [115], and even a diminution in the respiration rate of pests have also been reported [116].…”
Section: Mode Of Pesticidal Actionmentioning
confidence: 99%